Two new species of freshwater crabs of the genus Sundathelphusa Bott, 1969 (Decapoda: Brachyura: Gecarcinucidae) from caves in Luzon, Philippines - Husana, Daniel Edison M.; Yamamuro, Masumi; Ng, Peter K. L. (Zootaxa, 2014)
Two cave species of Sundathelphusa are described from a karst area in southern Luzon, Philippines. Both species have elongated ambulatory legs but the eyes and carapace pigmentation are well developed, indicating they are not troglobites. Sundathelphusa danae sp. nov. is superficially more similar to S. longipes (Balss, 1937) than to S. holthuisi Ng, 2010, which was described from the same locality. Sundathelphusa danae sp. nov. is distinguished from its closest congeners by its strongly convex anterolateral margin, more swollen branchial regions, possession of a complete frontal median triangle, laterally inflated subbranchial region and the more slender ambulatory legs. Sundathelphusa vienae sp. nov. is unusual among Sundathelphusa species in that its carapace is more quadrate, with the slender and almost straight male first gonopod tapered and having a pointed terminal segment.